Usefulness of raw bioelectrical impedance parameters in tracking fluid shifts in judo athletes - Silva, A. M.; Nunes, C. L.; Matias, C. N.; Rocha, P. M.; Minderico, C. S.; Heymsfield, S. B.; Lukaski, H.; Sardinha, L. B. (European Journal of Sport Science, 2020)
Bioelectrical impedance (BI) has been widely used but clarification about the behaviour of raw BI measurements under specific athletic conditions is required. Thus, we determined the usefulness of raw BI measures in tracking body fluids changes during the preparation period prior to competition in elite Judo athletes. At baseline (weight stability), 27 male athletes were evaluated (23.2 ± 2.8y) and again 1-3 days before competition (~1-2 months apart). Athletes were free to gain/lost weight based upon specific competition needs. Using dilution techniques (deuterium and bromide), total-body water (TBW) and extracellular water were estimated, and intracellular water calculated as TBW minus extracellular water. Body fluid distribution was determined as Extra-to-/Intracellular water (E/I). Fat and fat-free mass (FFM) was assessed by dual-energy x-ray absorptiometry. Resistance, reactance, and phase angle (PhA) were obtained from bioelectrical impedance spectroscopy (50-kHz frequency). No differences in raw BI measures were observed between athletes that lost (N = 17) or gain weight (N = 10), except for fat, FFM, extracellular water, and EI (p < 0.05). After adjusting for FFM and height, resistance explained TBW (ß = -0.047, p = 0.002) and extracelular water (ß = -0.025, p = 0.001). Reactance explained ECW (ß = -0.098, p = 0.004) and EI (ß = -0.004, p = 0.006), while PhA predicted TBW (ß = 1.609, p = 0.047), ICW (ß = 1.899, p = 0.001) and EI (ß = -0.056, p = 0.001). Regardless of body composition changes, athletes who increase reactance and resistance reduced extracellular water and body fluids while those who raised PhA increased intracellular water. Judo athletes who reduced weight, decreased FFM but cellular health was not compromised, as PhA remained stable and, consequently, cell hydration.